STUDY LITERATUR : GRAPHENE, NANO TEKNOLOGI SEBAGAI MATERIAL KONSTRUKSI MASA DEPAN - Apriansyah, Muh; Wangsa, Ananda Galang; Ukkasya, Muhamad; Fadlun, Fadlun; Anisah, Nur (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2024)
The development of science and technology encourages progress in various fields, especially through academic innovation. In 2010, Andre K. Geim and Konstantin Novoselov won the Nobel for their discovery of graphene; using tape and graphite. Graphen, known as nanotechnology; superior, has conductive, strong and elastic properties, with these superior properties making graphen a material that has great potential for use in construction activities, such as steel wire ropes for bridges. NASA plans a lift to space using graphene; because of his strength. This research analyzes publications from various sources such as Google Scholar, Dimension, and Research Gate, exploring the attributes of graphene and its derivatives to improve the properties of composite cements and future construction. With the same basic properties as Graphene, Graphene oxide (GO) is also able to increase the compressive, tensile and ductility strength of concrete, reduce cracking, provide electrical conductivity, increase corrosion resistance, and improve the workability of the concrete mixture. Although its use in construction has great potential to overcome future construction problems. However, to be able to use graphene in construction activities, it still requires a lot of development and research.